2008
DOI: 10.1055/s-2008-1027724
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy CT Angiography of the Lung in Patients with Suspected Pulmonary Embolism: Initial Results

Abstract: To evaluate the feasibility of dual-energy CT angiography (CTA) of the lung in patients with suspected pulmonary embolism (PE). 24 patients with suspected PE were examined with a single-acquisition, dual-energy CTA protocol (A-system: 140 kV/65 mAsref, B-system: 80kV/190 mAsref) on a dual-source CT system. Lung perfusion was visualized by color-coding voxels containing iodine and air using dedicated dual-energy postprocessing software. Perfusion defects were classified by two blinded radiologists as being cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 16 publications
4
97
0
Order By: Relevance
“…Thereby, DECT holds the potential to provide simultaneous information on the presence of endoluminal thrombus and lung perfusion impairment by generating iodine distribution maps of the lung parenchyma (▶ Fig. 4) [11,12,14,20,28,29]. The most recent technical advancements in DECT include a new powerful X-ray tube (Vectron tube, Siemens) in third generation scanners which allows for dual-energy examinations utilizing a new 90/Sn150 kV scan ▶ Table 5 Computed tomography pulmonary angiography: SSCT, DSCT, DECT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, DECT holds the potential to provide simultaneous information on the presence of endoluminal thrombus and lung perfusion impairment by generating iodine distribution maps of the lung parenchyma (▶ Fig. 4) [11,12,14,20,28,29]. The most recent technical advancements in DECT include a new powerful X-ray tube (Vectron tube, Siemens) in third generation scanners which allows for dual-energy examinations utilizing a new 90/Sn150 kV scan ▶ Table 5 Computed tomography pulmonary angiography: SSCT, DSCT, DECT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential of the latest (third) generation scanners to further decrease radiation dose while maintaining image quality has scarcely been assessed so far [18]. Concerning first and second generation DSCT scanners, DECT was reported to carry a radiation dose similar to that of conventional single-source CT (SSCT) [10,11,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has demonstrated the potential use of dual-energy CT (DECT) and different tube voltage/ tube current protocols for the characterization of tissue components and organ perfusion as well as for dose reduction [5][6][7][8][9][10][11]. In addition there is evidence that suggests the usefulness of DECT for comprehensive imaging of coronary artery disease and the evaluation of myocardial perfusion [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Various scanning protocols with dual source dual energy CT scanners have been proposed in the literature [Fink C, 2008], but currently there are few published protocols for CT systems of other vendors [Thieme SF, 2009]. The scan protocols recommended for dual-energy lung perfusion scans by dual-source CT Siemens are presented in Table 1.…”
Section: Scanning Protocolsmentioning
confidence: 99%